Postsynaptic Density Protein-95 Regulates NMDA Channel Gating and Surface Expression - Lin, Ying (J Neurosci, 2004)
NMDA receptors (NMDARs) colocalize with postsynaptic density protein-95 (PSD-95), a multivalent synaptic scaffolding protein and core component of the postsynaptic density, at excitatory synapses. Although much is known about the identity and properties of scaffolding proteins, little is known about their actions on NMDAR function. Here we show that association of PSD-95 with NMDARs modulates channel gating and surface expression. PSD-95 increases the number of functional channels at the cell surface and channel opening rate of NMDARs, with little or no change in conductance, reversal potential, or mean open time. We show further that PSD-95 increases NMDAR surface expression by increasing the rate of channel insertion and decreasing the rate of channel internalization. The PDZ (PSD-95, discs large, zona occludens-1) binding motif at the distal end of the NR2 C-terminal tail is critical to the actions of PSD-95 on NMDAR function and surface expression. Given that activity bi-directionally modifies synaptic levels of PSD-95, our findings suggest a novel mechanism for activity-dependent regulation of NMDARs at central synapses.